THE USE OF BIOCONSERVATISM BIOAMID-2 IN THE GREEN FODDER SILAGE - Nasambaev, E.G.; Sadykov, R.S.; Stepanova, T.S.; Azhaypova, I.G. (Западно-Казахстанский аграрно-технический университет имени Жангир хана, 2015)
The article discusses the use of biokonservanta "BIOAMID-2" in the green fodder silage. The results of the study of the chemical composition of corn silage and its effect on the productive qualities of Holstein breed were established.
Keywords: silage; milk productivity; biokonservative